A Landowner’s Introduction to the Forest Carbon Market - Natalia Medina Irizarry; Michael Andreu; Tamara Cushing (EDIS, 2022)
In recent years, carbon programs have emerged that allow forest landowners to receive payment for the ecosystem services their forests provide. The primary service of interest is carbon sequestration because it has been deemed one of the solutions to climate change. This publication serves as an introduction to the forest carbon market, how it works, common terminology used, and who some of the key players are.